2019
DOI: 10.3389/fpls.2019.00378
|View full text |Cite
|
Sign up to set email alerts
|

ATP as Phosphorus and Nitrogen Source for Nutrient Uptake by Fagus sylvatica and Populus x canescens Roots

Abstract: The present study elucidated whether roots of temperate forest trees can take up organic phosphorus in the form of ATP. Detached non-mycorrhizal roots of beech ( Fagus sylvatica ) and gray poplar ( Populus x canescens ) were exposed under controlled conditions to 33 P-ATP and/or 13 C/ 15 N labeled ATP in the presence and absence of the acid phosphatase inhibitor MoO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 90 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…By contrast, the low Pi:Po ratios at the P-poor site LUE could be indicative of the uptake of Po. In line, Scheerer et al (2019) showed that small P-containing organic molecules can be taken up directly (i.e., intact) by trees. Alternatively, low Pi:Po ratios might be indicative of tree-internal P cycling.…”
Section: Site Effects On P Concentrations and O Isotope Signatures Ofmentioning
confidence: 96%
“…By contrast, the low Pi:Po ratios at the P-poor site LUE could be indicative of the uptake of Po. In line, Scheerer et al (2019) showed that small P-containing organic molecules can be taken up directly (i.e., intact) by trees. Alternatively, low Pi:Po ratios might be indicative of tree-internal P cycling.…”
Section: Site Effects On P Concentrations and O Isotope Signatures Ofmentioning
confidence: 96%
“…Phosphorus is an important element necessary for plant growth and is a vital component in plant cell structure and energy production [ 33 ]. It is also a structural component of DNA and RNA, and a component of ATP (i.e., energy for metabolic processes) [ 34 , 35 , 36 ]. At the same time, phosphorus can also participate in the assimilation of plant photosynthesis and the phosphorylation of photosynthesis [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction Phosphorus (P), a macronutrient present in all living cells, is essential for plant growth and development because of its functions in energy transfer, in DNA in terms of inheritance, in membrane components, in carbon metabolism and in regulation and signaling [1]. The low availability of soil P and the acquisition of P exclusively through plant roots result in P being a major factor limiting plant growth and development.…”
mentioning
confidence: 99%